ICU Length of Stay and Factors Associated with Longer Stay of Major Trauma Patients with Multiple Rib Fractures: A Retrospective Observational Study - Hesham S. Abdelwahed; F. Eduardo Martinez (Critical Care Research and Practice)
Background. Chest injury with multiple rib fractures is the most common injury among major trauma patients in New South Wales (23%) and is associated with a high rate of mortality and morbidity. The aim of this study was to determine the intensive care unit (ICU) length of stay (LOS) among major trauma patients with multiple rib fractures and to identify factors associated with a prolonged ICU LOS. Materials and Methods. Single-centre, retrospective observational cohort study of adult patients with 3 or more traumatic rib fractures, who were admitted to ICU between June 2014 and June 2019. A comparison was made between patients who stayed in ICU for less than 7 days and those that stay for 7 or more days. Results. Among 215 patients who were enrolled, 150 (69.7%) were male, the median Injury Severity Score (ISS) was 24 (interquartile range (IQR): 17–32). The median ICU LOS was 4 (IQR: 2–7) days and the average ICU LOS was 6.5 (SD 8.5; 95% CI 5.3–7.6) days. The median number of rib fractures was 6 (IQR: 5–9) and 76 (35.3%) patients had a flail chest. Patients who stayed longer than 7 days in ICU had higher ISS, higher APACHE-II score, greater number of rib fractures, higher rate of lung contusions, and required more respiratory support of any type. Conclusions. ISS, number of rib fractures, lung contusion, and flail chest were associated with prolonged ICU LOS in patients with traumatic multiple rib fractures.